A photothermal conversion ion imprinted aerogel and a preparation method thereof

CN118059828BActive Publication Date: 2026-10-30CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410354757.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2026-10-30
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

然而,温度响应往往受到热源的渗透和热源的作用范围的限制

Benefits of technology

[0027](1)、利用纤维素纳米晶和氧化石墨烯为功能单体,丰富得羟基和羧基为接枝温敏单体和为离子印迹聚合物的固载提供位点。以此为功能单体制备的气凝胶提高吸附剂的吸附动力学;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118059828B_ABST
    Figure CN118059828B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of material preparation, and discloses a photo-thermal conversion ion imprinted aerogel and a preparation method thereof.CNCs and graphene oxide are used as bifunctional monomers, and a temperature-sensitive monomer NIPAM is grafted onto the surface of the CNCs by using ATRP technology.Coupling ion imprinting technology improves the adsorption selectivity of Dy.A squarylium cyanine is introduced as a photo-thermal conversion agent, and under NIR irradiation, the photo-thermal conversion agent converts light energy into heat energy and transmits the heat energy to NIPAM, so that the internal structure of the aerogel shrinks to realize rapid desorption of Dy(Ⅲ).The technical advantages of the present application are as follows: the internal connecting framework and highly ordered porous structure of the CNCs and graphene oxide composite aerogel can effectively improve the adsorption kinetic rate;the ion imprinting technology is used to fix specific cavities on the surface of the CNCs to achieve selective adsorption of Dy;the squarylium cyanine is used to convert light energy into heat energy and transmit the heat energy to the long chain of PNIPAM, so that the long chain changes from a relaxed state to a contracted state, thereby causing the volume of the network structure to shrink, resulting in changes in the pore structure of the aerogel and thus green desorption of Dy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials preparation technology, and in particular to a photothermal conversion ion-imprinted aerogel and its preparation method. Background Technology

[0002] Rare earth elements are closely related to key manufacturing sectors that my country will focus on developing in the future, such as high-end equipment manufacturing, new energy, new materials, and new energy vehicles. Meanwhile, permanent magnets with added dysprosium (Dy(III)) are widely used in clean production (new energy vehicles, energy-saving appliances, etc.) in the high-end market. Commonly used rare earth recovery methods include chemical precipitation, ion exchange, electrochemical methods, adsorption, and membrane separation. Adsorbents utilize their high specific surface area or functional groups to adsorb rare earth elements, and have received widespread attention due to their advantages of being green, fast, simple, inexpensive, and recyclable.

[0003] Secondary resources often contain two or more rare earth ions simultaneously, and most of these ions share similar physicochemical properties, leading to their simultaneous adsorption during the process. From a resource recycling perspective, this inevitably complicates the separation process and increases the cost of further processing. In recent years, novel ion imprinting techniques have been developed for the selective adsorption and separation of rare earth elements. This involves using the target ion as a template and constructing an imprinted polymer with a three-dimensional porous structure corresponding to the target metal ion through polymerization or condensation reactions, thus creating adsorption sites and specific recognition capabilities for the target ion.

[0004] However, the adsorption and desorption behaviors of these novel highly selective adsorbents are often difficult to balance. This is because highly selective adsorbents are typically difficult to desorb due to strong bonding. Currently, these highly selective adsorbents often employ acid washing to disrupt the chelation between the adsorbent and rare earth elements, thereby achieving desorption. However, the acidic wastewater generated by the acid washing process not only harms the soil and environment but also wastes recyclable resources in the acid washing waste liquid, greatly restricting the application of novel adsorbents. Therefore, establishing a new pollution-free adsorption-desorption process is of paramount importance.

[0005] In recent years, thermosensitive polymers have been widely used for drug release due to their reversible phase transitions or volume changes with ambient temperature. Inspired by this, it is hypothesized that rare earth element Dy(III) can be desorbed from adsorbents in a manner similar to drug release. However, temperature response is often limited by the penetration and range of the heat source. In contrast, photostimulation is widely used due to its advantages such as cleanliness, availability, remote operation, and precise and rapid response modulation. Therefore, we propose to utilize photothermal stimulation to induce self-heating in materials, thereby achieving internal structural contraction and realizing a green desorption process. We prepared ion-imprinted aerogels using cellulose nanocrystals and graphene oxide as functional monomers, which effectively improved adsorption kinetics and adsorption selectivity. In addition, we introduced the photothermal conversion material chlorine and the temperature-sensitive monomer N-isopropylacrylamide (NIPAM). Under irradiation with highly penetrating 808 nm near-infrared light, chlorine converts light energy into heat energy and transfers it to the PNIPAM chain, thereby causing the PNIPAM chain to contract and achieving green and rapid recovery of Dy(III). Summary of the Invention

[0006] The technical problem to be solved by this invention is to overcome the shortcomings of existing technologies and provide a photothermal conversion ion-imprinted aerogel and its preparation method. Utilizing cellulose nanocrystals and graphene oxide as functional monomers to provide adsorption sites, NIPAM is grafted using ATRP technology, and chlorine oxocyanate is introduced as a photothermal conversion material. Coupled with ion imprinting technology, a cellulose nanocrystal-graphene oxide photothermal conversion imprinted adsorbent material is prepared, thereby constructing an intelligent photothermal response system that achieves selective adsorption and green desorption of rare earth ions.

[0007] The technical solution adopted by this invention to solve its technical problem is:

[0008] A method for preparing photothermal conversion ion-imprinted aerogel specifically includes the following steps:

[0009] Step S1: Preparation of cellulose nanocrystals (CNCs)

[0010] Add defatted cotton to sulfuric acid solution at a solid-liquid ratio of 1g:15mL, stir in an oil bath at 45℃ for 3 hours, then pour into 10 times the volume of ice water and let stand overnight; centrifuge the lower phase suspension and purify by dialysis until the pH value of the cellulose nanocrystal suspension is greater than 2.4;

[0011] Step S2, Synthesis of ketone cyanine,

[0012] Weigh out an amount of 1,4-dicarboxyaniline and keto acid in a molar ratio of 1:(1.1-1.3) and place it in a mixed solution of acetone and water. Stir at 45°C for 3 days. The solution changes from pale yellow to brownish-red and a red solid precipitates out. After the reaction is complete, dilute with distilled water and centrifuge to obtain a brownish-red solid. Then wash with n-alkyl and place the obtained solid in an oven at 50°C to dry into a dark red solid.

[0013] Step S3, Ketocyanine-silane,

[0014] The ketocyanine obtained in step S2 was mixed with methanol at a solid-liquid ratio of 25 mg: 1 mL and sonicated for 5 min. 3-aminopropyltriethoxysilane (APTES) was added dropwise under stirring and reacted at room temperature for 24 h. The reaction was stopped with anhydrous ethanol and methanol was removed using a rotary evaporator to obtain ketocyanine-silane.

[0015] Step S4, the synthesis of cellulose nanocrystals grafted with temperature-sensitive monomers, includes:

[0016] Step S41: The cellulose nanocrystal suspension obtained in step S1 was centrifuged and replaced repeatedly in acetone and anhydrous tetrahydrofuran (THF) until it was finally dispersed in anhydrous tetrahydrofuran. Then, it was uniformly dispersed in the above suspension at a molar ratio of triethylamine to 4-dimethylaminopyridine (DMAP) of 10:1. 2-bromoisobutyryl bromide (BIB) was dissolved in anhydrous THF at a mass ratio of DMAP to BIB of 4:(4-6) and added dropwise to the above CNCs suspension using a constant pressure funnel. After the addition was completed, the three-necked flask was sealed with a rubber stopper and magnetically stirred. The reaction was carried out at 25°C in a N2 atmosphere for 24 hours. After the reaction was completed, the Br-CNCs were washed repeatedly with anhydrous THF, a mixture of anhydrous THF and anhydrous ethanol, and acetone to remove residual chemical reagents. The resulting Br-CNCs were dispersed in deionized water.

[0017] Step S42: Add the initiated Br-CNCs and methanol to a reaction flask. Pre-deoxygenate the mixture by evacuating and purging with nitrogen three times. Add NIPAM and CuBr to the deoxygenated Br-CNCs suspension at a mass ratio of Br-CNCs:N-isopropylacrylamide (NIPAM):cuprous bromide (CuBr) of 1:(29–54):(0.35–0.67). Seal the flask and cycle through freezing, evacuation, and thawing three times. Then, inject N,N,N',N',N″-pentamethyldiethyltriamine (PMDETA) into the reaction flask using a syringe at a mass ratio of Br-CNCs:PMDETA of 1:(0.41–0.59). Keep the flask sealed and react with magnetic stirring at 25°C for 24 hours. The product after the reaction, i.e., the thermosensitive modified CNCs (P-CNCs), is centrifuged and dialyzed multiple times and stored for later use.

[0018] Step S5: Synthesis of cellulose nanocrystal-graphene oxide photothermal conversion imprinted composite aerogel (P-ICA)

[0019] The P-CNCs solution obtained in step S4, graphene oxide, and Dy were mixed evenly in a ratio of (2-4) mL: 1 mg: 1.6 mg and allowed to stand for 2 hours. Then, the crosslinking agent tetraethyl orthosilicate (TEOS) and the ketone acid cyanosilane obtained in step S3 were added to the above mixed solution. The mixture was stirred at 30°C for 8 hours to form a hydrogel. Finally, P-ICA was obtained by supercritical drying. The obtained aerogel was placed in an appropriate amount of distilled water and Dy was removed by near-infrared irradiation for 2 hours. Finally, P-ICA containing Dy-specific cavities was obtained.

[0020] Furthermore, in step S1, sulfuric acid and distilled water are mixed in a volume ratio of 1:1 in the sulfuric acid solution.

[0021] Furthermore, the volume ratio of acetone to water in the mixed solution in step S2 is 1:1.

[0022] Furthermore, in step S3, the ratio of ketone cyanine and APTES is 122 mg: 1 mL.

[0023] Furthermore, in step S41, the volume ratio of anhydrous THF to anhydrous ethanol is 1:1.

[0024] Further, in step S5, the volume ratio of P-CNCs, TEOS, and chlorhexidine silane is 1:(0.027~0.053):(0.0003~0.002).

[0025] A photothermal conversion ion-imprinted aerogel was prepared using the method described above.

[0026] The beneficial effects of this invention are as follows: This invention has a reasonable design and a simple preparation method, and has the following advantages:

[0027] (1) Using cellulose nanocrystals and graphene oxide as functional monomers, abundant hydroxyl and carboxyl groups are obtained to provide sites for grafting thermosensitive monomers and for immobilizing ion-imprinted polymers. Aerogels prepared using these functional monomers improve the adsorption kinetics of the adsorbent;

[0028] (2) Coupled ion imprinting technology enables adsorbent materials to have Dy(Ⅲ) specific cavities and selective recognition;

[0029] (3) By changing the temperature to bring the temperature-sensitive monomer to a low critical dissolution temperature, PNIPAN changes from a relaxed state to a contracted state, thereby enabling the green separation of Dy(Ⅲ). Since aerogel has a thermal insulation effect, the near-infrared light-responsive photothermal conversion material ketone cyanine is used to convert light energy into heat energy and transfer it to the PNIPAN chain, making the material self-heating, thus solving the problems of heat source penetration and the limitation of the heat source's effective range. Attached Figure Description

[0030] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0031] Figure 1 Scanning electron microscope (SEM) images of NP-NCA(a), NP-ICA(b), P-NCA(c), and P-ICA(d) prepared in Example 1;

[0032] Figure 2 X-ray photoelectron spectra of P-ICA and NP-ICA prepared in Example 1;

[0033] Figure 3 The P-ICA, P-NCA, NP-ICA, and NP-NCA prepared in Example 1 and their adsorption of different rare earth ions;

[0034] Figure 4 Fitted adsorption isotherms of Dy(Ⅲ) adsorbed by P-ICA, P-NCA, NP-ICA and NP-NCA prepared in Example 1;

[0035] Figure 5 The images show the FT-IR spectra of P-ICA, P-NCA, NP-ICA, and NP-NCA after adsorption prepared in Example 1.

[0036] Figure 6 The effects of P-NCA and P-ICA prepared in Examples 1-3 on the adsorption of dysprosium ions and the imprinting factor IF;

[0037] Figure 7 The desorption rate of P-ICA prepared in Example 1 on Dy(Ⅲ) under 808nm near-infrared light irradiation;

[0038] Figure 8 The P-ICA (0, 0.5, 1.0, and 1.5 mg / L) prepared in Example 1 were irradiated with near-infrared light (808 nm, 1.0 W / cm²). 2Infrared thermogram under ) Detailed Implementation

[0039] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0040] It should be noted that the terminology used herein is for the purpose of describing particular implementations only and is not intended to limit the exemplary implementations according to this application. As used herein, the singular form includes the plural form unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this description, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0041] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0042] Example 1

[0043] A method for preparing photothermal conversion ion-imprinted aerogel specifically includes the following steps:

[0044] Step S1: Synthesis of cellulose nanocrystals (CNCs):

[0045] Weigh 10g of defatted cotton and place it in a mixed solution of 75mL sulfuric acid (95-98%) and 75mL water after cooling; stir in an oil bath at 45℃ for 4 hours, then pour it into 1.5L of ice water and let it stand for 15 hours; centrifuge the lower phase suspension and purify it by dialysis until the pH value of the suspension is greater than 2.4, thus obtaining 3wt% CNCs;

[0046] Step S2, Synthesis of ketone cyanine: Weigh 0.181 g of 1,4-dicarboxyaniline and 0.170 g of ketone acid into a 40 mL mixture of acetone and water (1:1 volume ratio) and stir at 45 °C for 3 days. The solution changes from pale yellow to brownish-red, and a red solid precipitates. After the reaction is complete, dilute with distilled water and centrifuge to obtain a brownish-red solid. Then wash with n-alkyl to remove some small polar impurities. Dry the resulting solid in a 50 °C oven to obtain a dark red solid.

[0047] Step S3: Synthesis of ketocyanine-silane.

[0048] 100 mg of chlortetracycline was dissolved in 4 mL of methanol and sonicated for 5 min. 0.82 mL of APTES was added dropwise with stirring, and the reaction was allowed to proceed at room temperature for 24 h. The reaction was finally stopped with anhydrous ethanol, and methanol was removed using a rotary evaporator to obtain chlortetracycline-silane.

[0049] Step S4

[0050] Step S41, Synthesis of Brominated CNCs: A suspension containing 1.00 g of CNCs was centrifuged and replaced repeatedly in acetone and anhydrous tetrahydrofuran (THF) until it was finally dispersed in anhydrous THF. Then, 2.57 mL of triethylamine (TEA) and 2.26 g of 4-dimethylaminopyridine (DMAP) were added to the suspension and dispersed evenly. 2.84 g of 2-bromoisobutyryl bromide (BIB) was dissolved in a certain amount of anhydrous THF and added dropwise to the CNCs suspension using a constant pressure funnel. After the addition was complete, a three-necked flask was sealed with a rubber stopper and magnetically stirred. The reaction was carried out at 25 °C under a N2 atmosphere for 24 h. After the reaction was complete, the flask was washed repeatedly with anhydrous THF, a 1:1 mixture of anhydrous THF and anhydrous ethanol, and acetone to remove residual chemical reagents. The obtained brominated CNCs (Br-CNCs) were dispersed in deionized water for later use.

[0051] Step S42, synthesis of CNCs-g-PNIPAM,

[0052] 0.30 g of the initiated Br-CNCs and an appropriate amount of methanol were added to a reaction flask. The flask was pre-vacuumed and purged with nitrogen, with three cycles of deoxygenation. 11.30 g of NIPAM and 0.143 g of CuBr were added to the deoxygenated Br-CNCs suspension. The flask was then sealed and subjected to a freeze-vacuum-thaw cycle three times. Subsequently, 0.173 g of N,N,N',N',N″-pentamethyldiethyltriamine (PMDETA) was injected into the reaction flask using a syringe. The flask was kept sealed and the reaction was magnetically stirred at 25°C for 24 h. The product after the reaction, i.e., the thermosensitive modified CNCs (denoted as P-CNCs), was centrifuged and dialyzed multiple times and stored for later use.

[0053] Step S5: Synthesis of cellulose nanocrystal-graphene oxide photothermal conversion imprinted composite aerogel (P-ICA)

[0054] 5 mg of graphene oxide was weighed and added to 15 mL of P-CNCs solution, 8 mg of Dy(III) was added and allowed to stand for 2 h; then 600 μl of crosslinking agent TEOS and 15 μl of ketocyanine-silane were added and stirred at 30 °C for 8 h to form a hydrogel; finally, P-ICA was obtained by supercritical drying; the obtained aerogel was placed in an appropriate amount of distilled water (1 mg / mL) and Dy(III) was removed by near-infrared irradiation for 2 h; finally, P-ICA containing Dy(III) specific cavities was obtained.

[0055] The cellulose nanocrystal-graphene oxide photothermal conversion non-imprinted composite aerogel (P-NCA) followed the same experimental procedure as the P-ICA in Example 1, but without the addition of Dy(Ⅲ).

[0056] The corresponding cellulose nanocrystal imprinted composite aerogel (NP-ICA) followed the same experimental procedure as the P-ICA in Example 1, but without grafting NIPAM and without adding chlorhexidine silane. Elution was performed using a 9:1 mixture of water and acetic acid.

[0057] The corresponding cellulose nanocrystal non-imprinted composite aerogel (NP-NCA) was prepared using the same experimental procedure as NP-ICA in Comparative Example 2, but without the addition of Dy(Ⅲ).

[0058] The SEM image of the aerogel prepared in this embodiment is shown below. Figure 1 As shown, Figure 1 (a)NP-NCA, Figure 1 (b)NP-ICA, Figure 1 (c)P-NCA, Figure 1 (d)P-ICA. From Figure 1 (d) It can be seen that P-ICA exhibits a coarser and more ordered fiber structure.

[0059] The above high-resolution spectra of P-ICA, NP-ICA, and the O1s and N1s spectra before and after P-ICA adsorption are shown in the figure. Figure 2 As shown. From Figure 2 As can be seen from the image, the four characteristic peaks belong to the four elements O 1s, C 1s, N 1s, and Si 2p in ICA, respectively. The significant increase in the content of C and N elements in P-ICA is mainly due to the introduction of NIPAM and ketone cyanine. Figure 2 The changes in the binding energy of the groups before and after adsorption in b and c indicate that the carbonyl, hydroxyl, and amide groups in P-ICA play a dominant role in the complexation of Dy(Ⅲ). Additionally, the amino groups in APTES that are not fully bonded to ketocyanine may also participate in the complexation of Dy(Ⅲ).

[0060] To investigate the selective adsorption properties of the imprinted aerogel, we selected Nd(III) and Er(III) as competing ions for Dy(III). The results are as follows: Figure 3As shown in the figure, it can be seen that the imprinted aerogel has a better adsorption capacity for Dy(Ⅲ) than the non-imprinted aerogel.

[0061] The effect of initial concentration on aerogel adsorption was studied using Dy(Ⅲ) solutions of different initial concentrations. Figure 4 The adsorption isotherms of the adsorbent material were obtained by fitting the adsorption process using the Langmuir and Freundlich models. Table 1 provides the fitting constants of the two models. It can be clearly seen that the adsorption performance of the imprinted aerogel is better than that of the non-imprinted aerogel because the ion imprinting technology provides Dy(III) recognition sites for the adsorbent material. The maximum adsorption capacity of P-ICA is 72.08 mg g. -1 .

[0062] Table 1 Adsorption equilibrium constants of the isotherm model

[0063]

[0064] Figure 5 The images show the FT-IR spectra of the aerogel prepared in Example 1 and the P-ICA after adsorption. The newly appearing peaks in the P-ICA spectrum are attributed to the amide NH deformation vibration of NIPAM or to ionic bonding between ketone cyanine and APTES. A new -COO- stretching vibration appears in ketone cyanine. There are no significant changes in the imprinting technique or the adsorbed functional groups.

[0065] Example 2

[0066] The difference from Example 1 is that:

[0067] Step S42, Synthesis of CNCs-g-PNIPAM: 0.30 g of the initiated Br-CNCs and an appropriate amount of methanol were added to a reaction flask. The flask was pre-treated by vacuuming and purging with nitrogen, cycling three times to remove oxygen. 8.70 g of NIPAM and 0.105 g of CuBr were added to the deoxygenated Br-CNCs suspension. The flask was then sealed and subjected to a freeze-vacuum-thaw cycle three times. Subsequently, 0.123 g of N,N,N',N',N″-pentamethyldiethyltriamine (PMDETA) was injected into the reaction flask using a syringe. The flask was kept sealed and the reaction was magnetically stirred at 25°C for 24 h. The product after the reaction, i.e., the thermosensitive modified CNCs (denoted as P-CNCs), was centrifuged and dialyzed multiple times and stored for later use.

[0068] Step S5: Synthesis of cellulose nanocrystal-graphene oxide photothermal conversion imprinted composite aerogel (P-ICA): 5 mg of graphene oxide was weighed and added to 15 mL of P-CNCs solution, followed by the addition of 8 mg of Dy(III) and standing for 2 h. Then, 400 μl of crosslinking agent TEOS and 5.0 μl of chlorine silane were added, and the mixture was stirred at 30 °C for 8 h to form a hydrogel. Finally, P-ICA was obtained by supercritical drying. The obtained aerogel was placed in an appropriate amount of distilled water (1 mg / mL), and Dy(III) was removed by near-infrared irradiation for 2 h. Finally, P-ICA containing Dy(III) specific cavities was obtained.

[0069] The experimental procedure for the corresponding cellulose nanocrystal-graphene oxide photothermal conversion non-imprinted composite aerogel (P-NCA) is the same as that for P-ICA, but without the addition of Dy(Ⅲ).

[0070] Example 3

[0071] The difference from Example 1 is that:

[0072] Step S42, Synthesis of CNCs-g-PNIPAM: 0.30g of the initiated Br-CNCs and an appropriate amount of methanol were added to a reaction flask. The flask was pre-vacuumed and purged with nitrogen, and the mixture was circulated three times to remove oxygen. 16.20g of NIPAM and 0.201g of CuBr were added to the deoxygenated Br-CNCs suspension. The flask was then sealed and subjected to a freeze-vacuum-thaw cycle three times. Subsequently, 0.252g of N,N,N',N',N″-pentamethyldiethyltriamine (PMDETA) was injected into the reaction flask using a syringe. The flask was kept sealed and the reaction was magnetically stirred at 25°C for 24 hours. The product after the reaction, i.e., the thermosensitive modified CNCs (denoted as P-CNCs), was centrifuged and dialyzed multiple times and stored for later use.

[0073] Step S5: Synthesis of cellulose nanocrystal-graphene oxide photothermal conversion imprinted composite aerogel (P-ICA): 5 mg of graphene oxide was weighed and added to 15 mL of P-CNCs solution, and 8 mg of Dy(III) was added and allowed to stand for 2 h. Then, 800 μl of crosslinking agent TEOS and 30.0 μl of chlorine silane were added and stirred at 30 °C for 8 h to form a hydrogel. Finally, P-ICA was obtained by supercritical drying. The obtained aerogel was placed in an appropriate amount of distilled water (1 mg / mL) and Dy(III) was removed by near-infrared irradiation for 2 h. Finally, P-ICA containing Dy(III) specific cavities was obtained.

[0074] The experimental procedure for the corresponding cellulose nanocrystal-graphene oxide photothermal conversion non-imprinted composite aerogel (P-NCA) is the same as that for P-ICA, but without the addition of Dy(Ⅲ).

[0075] Performance determination of photothermal conversion ion-imprinted composite aerogel:

[0076] The aerogels P-ICA and P-NCA prepared in Examples 1-3 were dispersed in 50 mg L, respectively. -1 After standing in the dysprosium ion stock solution for 24 hours, the adsorption performance of the photothermal conversion ion-imprinted composite adsorbent material for Dy(III) was tested. The results are shown in […]. Figure 6 .from Figure 6 As can be seen, the P-ICA imprinting factor prepared in Example 1 is the highest. We usually use the imprinting factor to represent the selective adsorption effect of imprinted materials. It can be seen that the smart photoresponsive imprinted composite aerogel prepared in Example 1 exhibits a more superior selective adsorption effect.

[0077] Saturated P-ICA aerogel was immersed in distilled water and subjected to near-infrared light (808 nm, 1.0 W / cm²). 2 Irradiate for 2 hours. Figure 7 The figure shows the desorption efficiency of P-ICA prepared in Example 1 for Dy(Ⅲ) under near-infrared light irradiation. As can be seen from the figure, the desorption rate of P-ICA increases rapidly within 30 min of near-infrared light irradiation and reaches equilibrium within 2 h, with a desorption rate of 87.69%.

[0078] To investigate the photothermal conversion properties of P-ICA, the P-ICA prepared in Example 1 was immersed in distilled water to form dispersions (0, 0.5, 1.0, and 1.5 mg / L). The temperature change after 10 min of near-infrared light irradiation is shown below. Figure 8 As shown, after 10 minutes of near-infrared light irradiation, the temperature increased to 45.4, 50.3, and 53.4 °C, respectively, all exceeding the LCST value of the material. This indicates that P-ICA has good photothermal conversion performance.

[0079] In summary, the present invention is rationally designed, has a simple preparation method, and has the following advantages:

[0080] (1) Using cellulose nanocrystals and graphene oxide as functional monomers, abundant hydroxyl and carboxyl groups are obtained to provide sites for grafting thermosensitive monomers and for immobilizing ion-imprinted polymers. Aerogels prepared using these functional monomers improve the adsorption kinetics of the adsorbent;

[0081] (2) Coupled ion imprinting technology enables adsorbent materials to have Dy(Ⅲ) specific cavities and selective recognition;

[0082] (3) By changing the temperature to bring the temperature-sensitive monomer to a low critical dissolution temperature, PNIPAN changes from a relaxed state to a contracted state, thereby enabling the green separation of Dy(Ⅲ). Since aerogel has a thermal insulation effect, the near-infrared light-responsive photothermal conversion material ketone cyanine is used to convert light energy into heat energy and transfer it to the PNIPAN chain, making the material self-heating, thus solving the problems of heat source penetration and the limitation of the heat source's effective range.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing photothermal conversion ion-imprinted aerogel, characterized in that: Specifically, the steps include the following: Step S1: Preparation of cellulose nanocrystals. Add defatted cotton to sulfuric acid solution at a solid-liquid ratio of 1g:15mL, stir in an oil bath at 45 °C for 3 hours, then pour into 10 times the volume of ice water and let stand overnight; centrifuge the lower phase suspension and purify by dialysis until the pH of the cellulose nanocrystal suspension is greater than 2.4; Step S2, Synthesis of ketone cyanine, Weigh out an amount of 1,4-dicarboxyaniline and keto acid in a molar ratio of 1:(1.1~1.3) and place it in a mixed solution of acetone and water. Stir at 45 °C for 3 days. The solution changes from pale yellow to brownish-red and a red solid precipitates out. After the reaction is complete, dilute with distilled water and centrifuge to obtain a brownish-red solid. Then wash with n-hexane and dry the obtained solid in an oven at 50 °C to obtain a dark red solid. Step S3, Ketocyanosilane, The ketocyanine obtained in step S2 was mixed with methanol at a solid-liquid ratio of 25 mg: 1 mL and sonicated for 5 min. 3-aminopropyltriethoxysilane was added dropwise under stirring, and the reaction was carried out at room temperature for 24 h. The reaction was stopped with anhydrous ethanol, and methanol was removed using a rotary evaporator to obtain ketocyanine-silane. Step S4, synthesis of cellulose nanocrystals grafted with temperature-sensitive monomers, includes: Step S41: The cellulose nanocrystal suspension obtained in step S1 was centrifuged and replaced multiple times in acetone and anhydrous tetrahydrofuran, and finally dispersed in anhydrous tetrahydrofuran. Then, it was uniformly dispersed in the above suspension at a molar ratio of triethylamine to 4-dimethylaminopyridine of 10:

1. 2-bromoisobutyryl bromide was dissolved in anhydrous tetrahydrofuran in advance at a mass ratio of 4-dimethylaminopyridine to 2-bromoisobutyryl bromide of 4:(4~6), and added dropwise to the above cellulose nanocrystal suspension using a constant pressure funnel. After the addition was completed, the three-necked flask was sealed with a rubber stopper and magnetically stirred. The reaction was carried out at 25 °C in a N2 atmosphere for 24 h. After the reaction was completed, the flask was washed multiple times with anhydrous tetrahydrofuran, a mixture of anhydrous tetrahydrofuran and anhydrous ethanol, and acetone to remove residual chemical reagents. The obtained brominated CNCs were dispersed in deionized water. Step S42: Add the initiated brominated CNCs and methanol to a reaction flask. Pre-deoxygenate the mixture by vacuuming and purging with nitrogen three times. Add N-isopropylacrylamide and cuprous bromide to the deoxygenated brominated CNCs suspension at a mass ratio of brominated CNCs:N-isopropylacrylamide:cuprous bromide of 1:(29~54):(0.35~0.67). Seal the flask and cycle through freezing, vacuuming, and thawing three times. Then, inject N,N,N',N″,N″-pentamethyldiethyltriamine into the reaction flask using a syringe at a mass ratio of Br-CNCs:PMDETA of 1:(0.41~0.59). Keep the flask sealed and react with magnetic stirring at 25 °C for 24 h. The resulting product, the thermosensitive modified CNCs solution, is centrifuged and dialyzed multiple times and stored for later use. Step S5: Synthesis of cellulose nanocrystal-graphene oxide photothermal conversion imprinted composite aerogel. The thermosensitive modified CNCs solution obtained in step S4, graphene oxide, and Dy(III) were mixed evenly in a ratio of (2~4) mL: 1 mg: 1.6 mg and allowed to stand for 2 h. Then, the crosslinking agent tetraethyl orthosilicate and the ketone acid cyano-silane obtained in step S3 were added to the above mixed solution and stirred at 30 °C for 8 h to form a hydrogel. Finally, P-ICA was obtained by supercritical drying. The obtained aerogel was placed in an appropriate amount of distilled water and Dy(III) was removed by near-infrared irradiation for 2 h. Finally, a cellulose nanocrystal-graphene oxide photothermal conversion imprinted composite aerogel containing Dy(III) specific cavities was obtained.

2. The method for preparing a photothermal conversion ion-imprinted aerogel according to claim 1, characterized in that: In step S1, 95% to 98% of the sulfuric acid and distilled water are mixed in a volume ratio of 1:

1.

3. The method for preparing a photothermal conversion ion-imprinted aerogel according to claim 1, characterized in that: The volume ratio of acetone to water in the mixed solution in step S2 is 1:

1.

4. The method for preparing a photothermal conversion ion-imprinted aerogel according to claim 1, characterized in that: In step S3, the ratio of ketone cyanine and 3-aminopropyltriethoxysilane is 122 mg: 1 mL.

5. The method for preparing a photothermal conversion ion-imprinted aerogel according to claim 1, characterized in that: In step S41, the volume ratio of anhydrous tetrahydrofuran to anhydrous ethanol in the mixture is 1:

1.

6. The method for preparing a photothermal conversion ion-imprinted aerogel according to claim 1, characterized in that: In step S5, the volume ratio of the thermosensitive modified CNCs solution, the crosslinking agent tetraethyl orthosilicate, and the chlorhexidine silane is 1:(0.027~0.053):(0.0003~0.002).

7. A photothermal conversion ion-imprinted aerogel, characterized in that: Prepared using the method described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Force-induced responsive polymer with multi-hybrid network structure

    CN111378172A

  • Aerogel for harvesting atmospheric water

    US20220280915A1